A new solving function optimization problems methods—Resonance Algorithm. (September 2021) - Yu, WenXin; Xiao, WeiHong
Abstract: The chorus shows its unique charm with its beautiful harmony, uniform rhythm, colorful layers and free and precise pitch. If the Harmony is compared to the body and the Rhythm is like a bone, the Intonation will be the flesh and blood of this "elf". This paper abstracts the chorus effect into a multivariate function, constructs the mathematical relationship between Intonation, Tempo, Harmony, Rhythm, and Intensity, A novel mathematical algorithm—Resonance Algorithm (RA) is proposed, which finds the optimal solution of the multivariate function in the chorus effect through the cooperation and information sharing between individuals in the group. In order to verify the correctness of the proposed method, the performance of RA algorithm is tested. Firstly, the ability to search for complex function is compared with GA, ACO, PSO, etc. The results show that RA has better ability to search for optimal value, and the accuracy of the optimal value is higher. Secondly, RA and PSO are not only combined with SVM and Gaussian process respectively, but also classification and data fitting are performed. The experimental results show that RA has the characteristics of adaptability and stability, no need to set parameters, and easy to implement.